Efektivitas Promosi Kesehatan Menggunakan Media Audiovisual Terhadap Keaktifan Lansia ke Posyandu Lansia - Andayani, Sri Astutik; Khotimah, Husnul; Desy, Sry; Trilianto, Arif Eko; Razaq, Hefniy (Jurnal Keperawatan Profesional, 2019)
Implemented posyandu elderly there are obstacles that often faced is low visit, one of cause factor is low of knowledge of elderly so that beneficiary of posyandu elderly still not maximal. The purpose of this research is to know the influence of health promotion about elderly posyandu by use audio visual media toward liveliness of elderly in following elderly posyandu. The design use in this research is Quasy Experimental with pretest-posttest with control design. This research was conducted at Maesan Bondowoso health center with 55 respondents with total sampling technique. This analysis used Wilcoxon and Mann-Whitney test. The results showed that health promotion was effective to increase the member of ekderly visit to the elderly health center with p value 0,000. Keywords  : Health Promotion, Elderly Health Centre, elderly active